Maylan and his toy top - Lee, Marcy Dans (Quezon City : Adarna House, 2013)
"Maylan found a toy top buried in the sand. Little did he know that this top would cause quite a catastrophe in Langit, Lupa and Ugsuban, and send Maylan to the horizon!"--Cover.
Keywords: Children's stories